Analysis of the profile of fish consumers in Gaspar (SC) (Research, Society and Development, 2021)
The municipality of Gaspar (SC) produces farmed fish, placing the municipality in sixth position in the state's production. Because of this economic importance, we sought to identify the preferences of Gaspar consumers in relation to fish meat. The methodology was based on an exploratory-descriptive study using an investigative instrument applied to a sample of the municipality's population. The results showed that the fish consumer of Gaspar is composed mostly of women, aged between 18 and 30 years, married marital status / stable union, with complete high school education and family income of 1.1 to 5 minimum wages. 88.4% consume fish, with preference for freshwater fish. Fish consumption is occasional, about 2 to 5 kg per family / month, among the reasons for consumption are: flavor, healthy eating and variation of the menu. The fish are purchased mainly in supermarkets and fish for payment and consumption takes place in consumers' homes. The preferred species is tilapia, in the form of a fillet, and the following aspects are considered during the purchase: appearance, price, form of storage and origin. Among the reasons for not consuming fish meat even more, the price stands out. The results point to the need for joint work between organizations working in fish farming to define training and dissemination strategies among the population, involving schools, the media, entrepreneurs and producers, to encourage sustainable local consumption.